Comparative Study of Stewardship of Road Traffic Injuries Prevention with a Focus on the Role of Health System; Three Pioneer Countries and Three Similar to Iran - Saber Azami-Aghdash; Homayoun Sadeghi-Bazarghani; Ramin Rezapour; Mahdiyeh Heydari; Naser Derakhshani (Bulletin of Emergency and Trauma, 2019)
Objective: To compare the stewardship of road traffic accidents (RTIs) prevention in three pioneer countries and three similar ones to Iran.Methods: In this descriptive comparative study, the United States of America, Sweden, and Brazil as the pioneer countries in RTIs prevention were compared to the India, Pakistan, and Turkey as the countries socioeconomically similar to Iran. Embase, PubMed, Scopus, IranDoc, IranMedex, SID, and MagIran were searched. Also a hand search conducted on websites and search engines using related keywords.Results: In the pioneer countries in RTIs prevention there was a delegation to a particular organization. In the other three countries a part of the Ministry of Transportation had the overall responsibility of RTIs. In Iran there was uncertainty in the stewardship of RTIs prevention. There was little evidence on the role and activities of health systems in RTIs prevention.Conclusion: It seems necessary to define a lead agency organization on RTIs prevention in Iran with sufficient authority and resources. This study also recommends conducting reliable studies to investigate the possible roles that the health system of a country can assume regarding the RTIs prevention.